Design, analysis and fabrication of seed machine / Muhammad Zakwan Zainol Arifen and Haszeme Abu Kasim - Zainol Arifen, Muhammad Zakwan; Abu Kasim, Haszeme (School of Mechanical Engineering, 2022)
This project is to design, analyse, and fabricate the seed machine. The seed machine is a machine that helps people to reduce back pain when planting seeds. This machine also helps the gardeners to make the sowing process time become shorter. Next, the machine will make it easy for the gardeners to manage and maintain. The seed machine applies a mechanical concept to operate. In order to realise and fabricate this project, there are several specific procedures or techniques to be used such as welding, milling, and etc. Next, Solidworks 2017 is used for designing the model and to perform simulation analysis. This machine will help in solving problems for gardeners. The process of making this machine takes about 9 to 10 weeks. Also, make engineering calculations to make sure the strength of the machine is seemingly. This machine will be a handful of tools and helpful for the sowing seeds process.